Final answer:
The value of the expression 7b - 4a + 6c when a = 2, b = 6, and c = 5 is 64.
Step-by-step explanation:
To find the value of the expression when a = 2, b = 6, and c = 5, you simply substitute these values into the given expression 7b - 4a + 6c and then calculate.
Substituting the given values, we have:
- 7b becomes 7 * 6 = 42
- 4a becomes 4 * 2 = 8
- 6c becomes 6 * 5 = 30
Therefore, the expression 7b - 4a + 6c becomes:
42 - 8 + 30.
Adding and subtracting these, we get:
42 + 30 = 72
72 - 8 = 64
The value of the expression when a = 2, b = 6, and c = 5 is therefore 64.